Flexible shielding layers for solar cells in space applications. Issue 28 (14th April 2016) - Feenstra, J.; van Leest, R. H.; Smeenk, N. J.; Oomen, G.; Bongers, E.; Mulder, P.; Vlieg, E.; Schermer, J. J.
ABSTRACT: The development of flexible, thin‐film, and high‐efficiency III–V solar cells enables the design of new flexible, lightweight solar arrays for space applications. A requirement for these solar panels is the replacement of the rigid coverglasses by a flexible shielding layer. In this work, three candidate materials based on commercially available polyimides and synthesized polysiloxanes for such a shielding layer are compared with respect to their ease of synthesis, transparency. Polysiloxanes based on methyltrimethoxysilane (MTMS) based siloxane (MBS) showed the best reproducibility in synthesis of layers of the required thickness of about 300 µm with sufficient transparency and was therefore selected for further analysis. It was demonstrated that the MBS material could be doped with Ce to increase the radiation hardness. Showing virtually no loss of volatile condensable components in outgassing tests it can be concluded that the properties MBS are found suitable for further space qualification testing. © 2016 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2016, 133, 43661. Abstract :